2021
DOI: 10.3390/biology10090842
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Gene Period Contributes to Diapause via GABAeric-Diapause Hormone Pathway in Bombyx mori

Abstract: Diapause is a developmental transition in insects based on seasonal adaptation to adversity; it is regulated by a circadian clock system and the endocrine system. However, the molecular node and its mechanism underlying the effects of these systems are still unclear. Here, a mutant of Bombyx mori with the circadian clock gene Period (Per) knocked out was constructed, which dramatically changed the classic diapause-destined pathway. Per-knockout silkworms powerfully attenuated, but could not completely block, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 80 publications
1
33
0
Order By: Relevance
“…Secretion of diapause hormone is promoted in oocytes destined for diapause by environmental perception of the mother pre-deposition. Significant work has dissected the regulation of B. mori diapause in relation to numerous aspects of physiology, including other endocrine molecules, but thus far diapause hormone appears to be exclusive to moths ( Ichikawa et al, 1997 ; Cui et al, 2021 ; Tsuchiya et al, 2021 ). While diapause hormone likely impacts lifespan, research in the biology of aging most clearly benefits from examination of mechanisms in diapause that are well-conserved.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Secretion of diapause hormone is promoted in oocytes destined for diapause by environmental perception of the mother pre-deposition. Significant work has dissected the regulation of B. mori diapause in relation to numerous aspects of physiology, including other endocrine molecules, but thus far diapause hormone appears to be exclusive to moths ( Ichikawa et al, 1997 ; Cui et al, 2021 ; Tsuchiya et al, 2021 ). While diapause hormone likely impacts lifespan, research in the biology of aging most clearly benefits from examination of mechanisms in diapause that are well-conserved.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…However, the expression patterns of both negative elements differed between p50T and Kosetsu. This may be caused by differences in B. mori strains since previous studies showed differing per and tim expression rhythms among tissues, stages, and strains (Cui et al, 2021; Ikeda et al, 2019, 2021; Iwai et al, 2006; Tao et al, 2017). In the per Δ2 strain, tim expression was upregulated at all time points ( P < 0.001, two-way ANOVA; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both mutants lost eclosion and hatching rhythms, indicating that core clock genes are indispensable for circadian rhythms in B. mori . In addition, two groups independently described per’s involvement in photoperiodic diapause induction (Cui et al, 2021; Ikeda et al, 2021). Ikeda et al demonstrated that per knockout in the Kosetsu strain abolishes photoperiod sensitivity during the larval stage and inhibits diapause egg production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study’s findings indicate that the clock genes per , tim , Clk , cyc , and cry2 are involved in temperature-dependent diapause induction. Involvement of clock genes in photoperiodic induction of diapause has been shown in various insects, including B. mori (e.g., Pavelka et al, 2003 ; Sakamoto et al, 2009 ; Ikeno et al, 2010 ; Merlin et al, 2013 ; Meuti et al, 2015 ; Cui et al, 2021 ; Ikeda et al, 2021 ). However, the role of clock genes in temperature-dependent diapause induction has not been shown.…”
Section: Discussionmentioning
confidence: 99%